Responses of Heart Rate Variability to Acute Pain After Minor Spinal Surgery: Optimal Thresholds and Correlation With the Numeric Rating Scale. Issue 2 (April 2015) - Sesay, Musa; Robin, Georges; Tauzin-Fin, Patrick; Sacko, Oumar; Gimbert, Edouard; Vignes, Jean-Rodolphe; Liguoro, Dominique; Nouette-Gaulain, Karine
Abstract : Background: The autonomic nervous system is influenced by many stimuli including pain. Heart rate variability (HRV) is an indirect marker of the autonomic nervous system. Because of paucity of data, this study sought to determine the optimal thresholds of HRV above which the patients are in pain after minor spinal surgery (MSS). Secondly, we evaluated the correlation between HRV and the numeric rating scale (NRS). Methods: Following institutional review board approval, patients who underwent MSS were assessed in the postanesthesia care unit after extubation. A laptop containing the HRV software was connected to the ECG monitor. The low-frequency band (LF: 0.04 to 0.5 Hz) denoted both sympathetic and parasympathetic activities, whereas the high-frequency band (HF: 0.15 to 0.4 Hz) represented parasympathetic activity. LF/HF was the sympathovagal balance. Pain was quantified by the NRS ranging from 0 (no pain) to 10 (worst imaginable pain). Simultaneously, HRV parameters were noted. Optimal thresholds were calculated using receiver operating characteristic curves with NRS>3 as cutoff. The correlation between HRV and NRS was assessed using the Spearman rank test. Results: We included 120 patients (64 men and 56 women), mean age 51±14 years. The optimal pain threshold values were 298 ms 2 for LF and 3.12 for LF/HF, with no significant change in HF. NRS was correlated with LF (r=0.29, P <0.005) and LF/HF (r=0.31, P <0.001) but not with HF (r=0.09, NS). Conclusions: This study suggests that, after MSS, values of LF>298 m 2 and LF/HF>3.1 denote acute pain (NRS>3). These HRV parameters are significantly correlated with NRS.